Development Of Canva-Based Comic Teaching Materials For Concept Mastery And Critical Thinking Skills Of Vocational High School 5 Yogyakarta Students - Wulandari, Desi; Rochayati , Umi (Ridwan Institute, 2025)
Mastery of narrative texts plays an important role in learning English in vocational schools, but in reality many students still encounter obstacles in understanding the content of reading, recognizing the structure of the story, and honing critical thinking skills. Conventional learning tends to involve students less actively in exploring the meaning and moral message of the texts studied. This emphasizes the need for teaching material innovations that are more interactive, contextual, and relevant to the characteristics of students in vocational schools. This research aims to develop teaching materials in the form of Canva-assisted digital comics which are expected to support students' understanding of concepts and critical thinking skills. The method used refers to the Research and Development (R&D) approach with the Borg and Gall model which includes the planning stage, initial product development, limited trials, revisions, field tests, and product improvements. The subject of the study is a class X student at one of the State Vocational Schools in Yogyakarta, with data collection techniques through pretest and posttest. The validation of the instrument was carried out by media experts and material experts, whose results showed that the teaching materials were in the category of suitable for use, with the Aiken index of 0.73 and 0.75, respectively. The results of the analysis of learning effectiveness with the N-Gain formula showed a significant increase, namely a concept mastery score of 0.77 and critical thinking skills of 0.70, both of which are classified as high. These findings prove that Canva-based digital comics teaching materials are not only feasible, but also effective in supporting the understanding of narrative text materials while developing students' critical thinking skills. Therefore, this product is recommended to be integrated in English learning in vocational schools and can be a reference for the development of similar media.